2018
DOI: 10.1002/pc.25115
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of a novel hydrophilic PVDF/PVA/Al2O3 nanocomposite membrane for removal of As(V) from aqueous solutions

Abstract: In this study, the novel Poly(vinylidene fluoride)(PVDF)/ polyvinyl alcohol (PVA)/Al2O3 nanocomposite blend membranes with hydrophilic surface were prepared for the first time and used for removal of Arsenic from aqueous environments. First, PVDF/PVA blend membranes were prepared via Non-solvent-Induced Phase Separation method and then the characterization was done by several methods. Presence of PVA in membrane matrix caused significant improvements in hydrophilicity and permeability. Although the water conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Various treatment methods such as chemical precipitation, membrane filtration [4], oxidation-precipitation [5], coagulation-flocculation associated to filtration [6], sorption [7,8], nanofiltration [9,10], ion exchange [11], reverse osmosis [12], etc. have been utilized for the removal of As from contaminated potable water.…”
Section: Introductionmentioning
confidence: 99%
“…Various treatment methods such as chemical precipitation, membrane filtration [4], oxidation-precipitation [5], coagulation-flocculation associated to filtration [6], sorption [7,8], nanofiltration [9,10], ion exchange [11], reverse osmosis [12], etc. have been utilized for the removal of As from contaminated potable water.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In recent years, heavy metal pollution has increased as a result of the evolution of the chemical industry and the introduction of toxic compounds into water. [24][25][26][27][28][29] These elements, which have low biocompatibility and biodegradability, contain many compounds, but studies have shown that the contamination of arsenic has attracted much attention due to its effects on organisms and has become a global concern. [30] Arsenic causes many environmental and health problems and plays a key role in the development of cancer in the skin, lungs, bladder, and kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8‐23 ] In recent years, heavy metal pollution has increased as a result of the evolution of the chemical industry and the introduction of toxic compounds into water. [ 24‐29 ] These elements, which have low biocompatibility and biodegradability, contain many compounds, but studies have shown that the contamination of arsenic has attracted much attention due to its effects on organisms and has become a global concern. [ 30 ]…”
Section: Introductionmentioning
confidence: 99%
“…Most of the heavy metal ions have adverse toxic and carcinogenic effects on human being even at very low concentration as they gradually accumulate in the body parts through the drinking water over the time. [9,10] Among all the heavy metal ions, non-biodegradable ions especially Arsenic (As(V)) in potable drinking water cause acute global problem owing to their adverse impact on the environment and health. [11][12][13] The arsenic contamination problem is especially acute in developing parts of the world where the water treatment infrastructure may not be capable of providing suitable treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Organic dyes are also considered as serious pollutants as they can damage liver, digestive and central nervous systems of human beings. Most of the heavy metal ions have adverse toxic and carcinogenic effects on human being even at very low concentration as they gradually accumulate in the body parts through the drinking water over the time . Among all the heavy metal ions, non‐biodegradable ions especially Arsenic (As(V)) in potable drinking water cause acute global problem owing to their adverse impact on the environment and health .…”
Section: Introductionmentioning
confidence: 99%